Subject Explorer 3D: A Virtual Reality Collection Browsing and Searching Tool - Julien, Charles-Antoine; Guastavino, Catherine; Bouthillier, France; Leide, John E. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Controlled vocabulary is known to help searchers and Semantic Web ontologies are one of its latest incarnations. Unfortunately, many searchers are unaware of this useful organization of information. An interactive 3D fly-through search and browsing prototype was developed and is proposed as potential solution to enhance navigation. Le vocabulaire contrôlé est reconnu pour aider les chercheurs et les ontologies du web sémantique en sont la dernière incarnation. Malheureusement, nombre de chercheurs ne connaissent pas cet utile outil d'organisation de l'information. Un prototype interactif de recherche et de navigation en 3D a été développé et est proposé comme solution pour rehausser la navigation.